3D printing of a lithium-calcium-silicate crystal bioscaffold with dual bioactivities for osteochondral interface reconstruction. (March 2019) - Chen, Lei; Deng, Cuijun; Li, Jiayi; Yao, Qingqiang; Chang, Jiang; Wang, Liming; Wu, Chengtie
Abstract: It is difficult to achieve self-healing outcoming for the osteochondral defects caused by degenerative diseases. The simultaneous regeneration of both cartilage and subchondral bone tissues is an effective therapeutic strategy for osteochondral defects. However, it is challenging to design a single type of bioscaffold with suitable ionic components and beneficial osteo/chondral-stimulation ability for regeneration of osteochondral defects. In this study, we successfully synthesized a pure-phase lithium calcium silicate (Li2 Ca4 Si4 O13, L2 C4 S4 ) bioceramic by a sol-gel method, and further prepared L2 C4 S4 scaffolds by using a 3D-printing method. The compressive strength of L2 C4 S4 scaffolds could be well controlled in the range of 15–40 MPa when pore size varied from 170 to 400 μm. L2 C4 S4 scaffolds have been demonstrated to possess controlled biodegradability and good apatite-mineralization ability. At a certain concentration range, the ionic products from L2 C4 S4 significantly stimulated the proliferation and maturation of chondrocytes, as well as promoted the osteogenic differentiation of rBMSCs. L2 C4 S4 scaffolds simultaneously promoted the regeneration of both cartilage and subchondral bone as compared to pure β-TCP scaffolds in rabbit osteochondral defects. These findings suggest that 3D-printed L2 C4 S4 scaffolds with such specific ionic combination, high mechanical strength and good degradability as well as dual bioactivities, represent a promising biomaterial for osteochondral interface reconstruction. Graphical abstract: 3D-printed Li2 Ca4 Si4 O13 scaffolds possess dual bioactivities and can biologically fulfill the requirements of both cartilage and subchondral bone interface reconstruction, which represents a feasible strategy for osteochondral reconstruction.Image 1